Acute exposure to a sublethal dose of imidacloprid and coumaphos enhances olfactory learning and memory in the honeybee Apis mellifera - Williamson, Sally M. (Springer-Verlag, 2012)
The decline of honeybees and other pollinating insects is a current cause for concern. A major factor implicated in their decline is exposure to agricultural chemicals, in particular the neonicotinoid insecticides such as imidacloprid. Honeybees are also subjected to additional chemical exposure when beekeepers treat hives with acaricides to combat the mite Varroa destructor. Here, we assess the effects of acute sublethal doses of the neonicotinoid imidacloprid, and the organophosphate acaricide coumaphos, on honey bee learning and memory. Imidacloprid had little effect on performance in a six-trial olfactory conditioning assay, while coumaphos caused a modest impairment. We report a surprising lack of additive adverse effects when both compounds were administered simultaneously, which instead produced a modest improvement in learning and memory.